Evaluación de las emisiones de monóxido de carbono en la producción de ladrillos en el sector Tres Marías - Chone - Chinga Pinargote, Carlos Junior (2022)
The present study had as an objective to evaluate the emissions of Carbone Monoxide (CO) in the handcrafted production of bricks in the area Tres Marias-Chone. Interviews to the brickyards owners in the zone under study were carried out to collect information about the productive process, determining that the four-brickyards of the sector apply the same methodology, which is an ancestral practice. For the emission estimation of the CO, the fourth brickyard (L4) with a weekly production of approximately 14000 bricks was selected, this evaluation was made the first day of bricks cooking in the afternoon, simulating an isokinetic sampling with the methods of the EPA (1997) CTM 13, CTM 30, CTM 34, taking eight measurements with intervals of tree minutes, and giving as a result 3.621,9 mg/Nm3 of the emitted CO in the cooking process. This value exceeds the 1800 mg/Nm3 of the CO established by the Ecuadorian Environmental Regulations (TULSMA) as the maximum acceptable limit for pollutants emission from the combustion fixed sources, included the opened combustion sources. Next, it was proceeded with the design of an MK3 ecological kiln, which allows to take advantage of the generated heat during the cooking process of the bricks, and it was proposed to the producers like a measure for the emissions mitigation since they are reduced in 50%.